Red Blood Cells as Potential Repositories of MicroRNAs in the Circulatory System - Sun, Liping; Yu, Yang; Niu, Beifang; Wang, Deqing (Frontiers in Genetics, 2020)
The amount of erythrocyte-derived microRNA (miRNA) represents the majority of miRNA expression in whole blood. miR-451, miR-144, and miR-486, which are abundant in red blood cells (RBCs), are involved in the process of erythropoiesis and disease occurrence. Moreover, erythrocyte-derived miRNAs are reported to have the potential to be biomarkers of some diseases. However, it is still unclear if miRNAs derived from erythrocyte function and mechanisms related to this. Based on a review of previously published literature, we discussed several possible pathways by which RBC miRNAs may exert functions, and proposed that RBCs may serve as repositories of miRNAs in the circulatory system and participate in the regulation of gene expression mainly via the transfer of miRNAs from erythrocyte extracellular vesicles. Although the expression levels of RBC-derived miRNAs are high, there are still other important cell types such as leukocytes and platelets harboring functional miRNAs in the whole blood. Whether RBCs can be used as dynamic miRNA repositories, play roles in the regulation of the body normally, but regulate the whole circulatory system under the pathological states, needs a lot of experimental researches to prove.